Natural Killer Cell Functions during the Innate Immune Response to Pathogenic Streptococci - Lemire, Paul; Galbas, Tristan; Thibodeau, Jacques; Segura, Mariela (Frontiers in Microbiology, 2017)
Dendritic cells (DCs) and NK cells play a crucial role in the first phase of host defense against infections. Group B Streptococcus (GBS) and Streptococcus suis are encapsulated streptococci causing severe systemic inflammation, leading to septicemia and meningitis. Yet, the involvement of NK cells in the innate immune response to encapsulated bacterial infection is poorly characterized. Here, it was observed that these two streptococcal species rapidly induce the release of IFN-γ and that NK cells are the major cell type responsible for this production during the acute phase of the infection. Albeit S. suis capacity to activate NK cells was lower than that of GBS, these cells partially contribute to S. suis systemic infection; mainly through amplification of the inflammatory loop. In contrast, such a role was not observed during GBS systemic infection. IFN-γ release by NK cells required the presence of DCs, which in turn had a synergistic effect on DC cytokine production. These responses were mainly mediated by direct DC-NK cell contact and partially dependant on soluble factors. Though IL-12 and LFA-1 were shown to be critical in S. suis-mediated activation of the DC-NK cell crosstalk, different or redundant molecular pathways modulate DC-NK interactions during GBS infection. The bacterial capsular polysaccharides also differently modulated NK cell activation. Together, these results demonstrated a role of NK cells in the innate immune response against encapsulated streptococcal infections; yet the molecular pathways governing NK activation seem to differ upon the pathogen and should not be generalized when studying bacterial infections.